KEMAMPUAN REPRESENTASI MATEMATIS SISWA DALAM MATERI FUNGSI DI KELAS VIII SMP BUMI KHATULISTIWA - Herlina, .; Yusmin, Edy; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractRepresentation is central to study of mathematics. Students can develop and deepen their understanding of mathematical concepts and relationships as they create, compare, and use various representations. This research aimed to evaluate the students? ability of mathematical representation on the function subject matter. The subjects of this research were the students who had learn the function subject matter, they were grade VIII students of SMP Bumi Khatulistiwa. The method which used in this research was a descriptive  with case study. The technique of data collection were measurement technique and the direct communication technique. Based on the data analysis, generally the students? ability of mathematical representation in the middle categorized. The students could not represent the data correctly because the writer still found an error of their writing. According to the three types of representation which used such as visual representation, verbal representation and symbolic representation, the highest mean score was symbolic representation it was 16,07 ( 44,64%). Keywords: The Ability of Mathematical Representation, Function Subject Matter